Feasibility Study of Power Line Communications for Backhauling Outdoor Small Cells - Cortés-Arrabal, José Antonio; Cañete-Corripio, Francisco Javier; Toril-Genovés, Matías; Martos-Naya, Eduardo; Poncela-González, Javier; Díez-del-Río, Luis; García Mozos, Alicia (IEEE, 2021)
Small cells are low-power and low-range radio access nodes that can be used to increase network capacity in reduced areas with high trafﬁc demand and to provide coverage to small isolated zones. As their number is expected to be very high, connecting them to the aggregation point in a cost-efﬁcient manner is a key challenge, and there is consensus that none of the current technologies is valid for all scenarios. Since lamp-posts are one of the most convenient locations for outdoor small cells, this work analyzes the use of power line communications (PLC) over outdoor public lighting networks (OPLN) as a backhaul technology for outdoor small cell deployments. To this end, the characteristics of the PLC channels established in OPLN are ﬁrstly assessed. The analysis combines noise measurements performed in existing OPLN and channel responses obtained from a multiconductor transmission line (MTL) model. The attenuation, delay spread and spatial correlation of the multiple-input multiple-output (MIMO) channels are investigated and their inﬂuence in the physical layer parameters of PLC systems is discussed. Afterward, the performance achieved by state-of-the-art PLC systems is assessed. To this end, estimations obtained by means of simulations and measurements taken in actual networks are included. Data throughput achieved by PLC systems based on the ITU-T G.hn standard, as well as the expected improvements obtained by 3 × 3 MIMO systems, are given. Results indicate that PLC can be an interesting technology for coverage-driven small cell deployments with backhaul length shorter than 150 m, offering throughput values similar to existing Sub-6 GHz wireless solutions in non-line-of-sight (NLOS) conditions and wired ones like G.fast.
Keywords: Alumbrado público; Líneas eléctricas; Power line communications; Backhaul; Small cells; Outdoor public lighting networks